Uppvärmning av Almunge brandstation med pyrolys - Eriksson, Felix; Gustafsson, Erik; Malmberg, Karl; Martelius, Simon; Johansson, Simon; Johansson, Patrick; Stanowski, Michael (SLU/Dept. of Energy and Technology, 2019)
This project has been carried out on the behalf of Ihus in collaboration with Stuns Energi. The goal was to ﬁnd and model a solution based on the process of pyrolysis that can deliver enough heat to Almunge ﬁre station while storing maximum amount of CO2 in the form of biochar. Two systems that primarily used waste heat from a pyrolysis reactor were studied. In one case a wood pellet boiler was used to cover peak load and the second system used a coal boiler that uses some of the coal produced in the reactor. The result shows that both solutions can theoretically deliver the required amount of heat and have lower emissions of carbon dioxide than the current method of heat generation used on the property, a wood pellet boiler. A model of the system that uses a coal boiler shows that it, under a period of one year, releases 5 % more CO2, has a 60 % higher amount of unused waste heat, and consumes 22 % more substrate per month than the system that uses a wood pellet burner. However, the coal boiler resulted in 18 % higher in biochar production, potentially 33 % more coal bound if the produced biochar is used as a carbon sink, and 18 % higher economical value after 20 years.